A comparison of the effects of cinnamon, ginger, and metformin consumption on metabolic health, anthropometric indices, and sexual hormone levels in women with poly cystic ovary syndrome: A randomized double-blinded placebo-controlled clinical trial - Dastgheib, Marsa; Barati-Boldaji, Reza; Bahrampour, Niki; Taheri, Reihane; Borghei, Mohammad; Amooee, Sedigheh; Mohammadi-Sartang, Mohsen; Wong, Alexei; Babajafari, Siavash; Mazloomi, Seyed Mohammad (Frontiers in Nutrition, 2022)
Background/objectives Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder in women that can alter blood glucose, lipid profile and sexual hormonal level. Therefore, the evaluation of potential therapeutic agents in this population is important. The aim of the study was to determine the effects of cinnamon, ginger, and metformin intake on improvement of sex hormones level, metabolic health (lipid profiles, insulin level and fasting blood glucose) and anthropometric indices (weight, body mass index (BMI), etc) in women with PCOS. Methods 100 women with PCOS were randomly assigned to one of the following four groups: cinnamon (500 mg of cinnamon, 3 x day), ginger (500 mg of ginger, 3 x day), metformin (500 mg of metformin 3 x day) or placebo. However, 17 participants were excluded for various reasons and consequently, 83 participants were considered for analysis. Sexual hormones, anthropometrics, glycemic and lipid markers were evaluated before and after the 8-week intervention. Results Weight and BMI decreased significantly in all intervention groups. The consumption of metformin and cinnamon significantly decreased insulin resistance (HOMA-IR) in comparison to the placebo and ginger groups (P<0.05). Moreover, a significant decrease in FSH (follicle-stimulating hormone) and LH (Luteinizing hormone) levels were observed in the ginger compared to the placebo group. While metformin and cinnamon significantly lowered testosterone levels (P<0.05), none of the groups experienced a significant change in DHEA (dehydroepiandrosterone). Conclusion Our findings suggest that in women with PCOS, cinnamon supplementation causes similar reductions in insulin resistance and testosterone level to that of metformin. Ginger supplementation decreased FSH and LH , hormonal effects not seen following metformin consumption. Overall, cinnamon and ginger supplementations may potentially be used as alternative treatment in women with PCOS.